2006
DOI: 10.1111/j.1365-2141.2006.06036.x
|View full text |Cite
|
Sign up to set email alerts
|

Max Schultze (1865), G. Bizzozero (1882) and the discovery of the platelet

Abstract: SummaryMax Schultze published the first accurate and convincing description of platelets as part of a study devoted mainly to the white blood cells in 1865. He recognised them as a normal constituent of the blood and 'enthusiastically recommended' them as an object for further study by 'those concerned with the in-depth study of the blood of humans'. In 1882, Bizzozero demonstrated the value of this recommendation in his much more comprehensive study. He observed them microscopically in the circulating blood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 10 publications
(14 reference statements)
1
60
0
Order By: Relevance
“…4,5 Although platelets circulate throughout the body and participate in the control of hemostasis, increased platelet counts and activation of the coagulation cascade are often seen in cancer patients. 6,7 In addition, several studies indicate a role for platelets in promoting metastatic disease. These studies using mouse models of metastasis demonstrated that induction of thrombocytopenia, with antiplatelet antibodies or by injecting neuraminidase before tumor cell inoculation, significantly reduced the formation and overall number of lung metastases.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Although platelets circulate throughout the body and participate in the control of hemostasis, increased platelet counts and activation of the coagulation cascade are often seen in cancer patients. 6,7 In addition, several studies indicate a role for platelets in promoting metastatic disease. These studies using mouse models of metastasis demonstrated that induction of thrombocytopenia, with antiplatelet antibodies or by injecting neuraminidase before tumor cell inoculation, significantly reduced the formation and overall number of lung metastases.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of blood platelets and their pivotal role in thrombosis and hemostasis emerged about 150 years ago [1]. Within the last 15 years it became more and more evident that nonnucleated platelets are also implicated in the adaptive [2] as well as being components of the innate immune system [3,4], the latter which came into focus by the discovery that platelets express Toll-like receptors (TLRs) [5], of which TLR4, TLR2, and TLR9 were found to be the most abundant [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…He recommended these "normal constituents of blood" as an area of further in-depth study [ 4 ]. The Italian pathologist Giulio Bizzozero rose to the challenge.…”
Section: Synopsis Of Current Knowledge Historical Knowledgementioning
confidence: 99%